Prolonged worklife among grandfathers: Spillover effects on grandchildren's educational outcomes - Jim Been; Anne C. Gielen; Marike Knoef; Gloria Moroni (Tinbergen Institute, 2022)
Recent policies aiming to prolong worklives have increased older males' labor supply. Yet, little is known about their intergenerational effects. Using unique Dutch administrative data covering three consecutive generations, this paper studies the impact of increased grandfathers' labor supply following a reform in unemployment insurance for persons aged 57.5+ on grandchildren's educational performance. We find that increased grandfathers' labor supply increases grandchildren's test scores in 6th grade. The effect is driven by substitution of grandparents' informal care by formal childcare.
Keywords: J13; J14; J22; J26; J65; 330; Intergenerational effects; labor supply; unemployment insurance; child care; child development